Assessing Connectivity Thresholds Under Habitat Loss Scenarios for Threatened Amphibians and Squamate Reptiles in the Eastern Brazilian Amazon - Cássia Teixeira; Gisele Lopes Nunes; Leonardo Carreira Trevelin; Daniel Paiva Silva; Ana Lúcia da Costa Prudente (Ecology and Evolution, 2025)
ABSTRACT The extinction threshold hypothesis proposes a minimum of 30% habitat in a landscape to prevent isolation from affecting populations to local extinction. In this study, we tested scenarios of habitat loss in the landscape to evaluate whether the 30% habitat threshold is a good predictor of functional connectivity for 14 terrestrial herpetofauna species in eastern Brazilian Amazon landscapes. We evaluated functional connectivity across various habitat loss scenarios, utilizing species distribution models and landscape connectivity indices. We were able to demonstrate that below 32% habitat, overall regional connectivity in Southeastern Amazonia erodes, disturbing the ability of species to track environments within their climatic limits. However, species inhabiting montane savannahs in the region did not respond well to this 30% threshold and required the presence of sufficient areas to assess a possible decline. We also discovered that, when evaluated together, small patches in the landscape contributed to the integral connectivity of the study area and may demonstrate their importance as links between larger patches. Our results provide critical insights into the conservation needs of forest and montane savannah species, highlighting that while forest species adhere closely to a habitat threshold, montane savannah species require a different approach for conservation.